Temporal variability in stable isotope ratios of C and N in the vibrissa of captive and wild adult South American sea lions Otaria byronia : More than just diet shifts - Cardona, Luis (2017)
We analyzed the d13C and d15N values in the vibrissae of captive adult breeding South American sea lions (Otaria byronia) fed at a constant diet and then used thisinformation to analyze the change in stable isotope values along the vibrissae from wild individuals. The overall diet-to-vibrissa discrimination factor of the captive animals was 3.0& 0.1& for d13C and 3.6& 0.1& for d15N, but the stable isotope ratios fluctuated periodically despite constant diet. The d13C and d15N valuesof the captive male declined at the end of the breeding season, whereas the d13C values of the female increased during the central part of pregnancy and the d15N valuespeaked during lactation. The d13C and d15N values of adult wild specimens alsofluctuated periodically and vibrissae growth rate (0.15 mm/d in both sexes) was slightly lower than in captivity (0.17 mm/d), assuming an annual periodicity foroscillations. Similarities in the amplitude of the cycles of captive and wild males suggested that fasting was probably the main source of periodic variability in the d15N of wild males, whereas pregnancy and lactation were probably the main source of periodic variability for the d13C of wild females.